Investigating the Reason why Tourists Revisit Thailand - SARAITHONG, Wuthiya; CHANCHAROENCHAI, Kanokwan (Journal of Environmental Management and Tourism; Vol 8 No 6 (2017): JEMT Volum VIII Issue 6(22) Fall 2017, 2018)
In recent years, the performance of Thailand’s tourism sector has been unstable due to a number of unfortunate situations, e.g. worldwide economic recession, natural disaster. To make this sector more sustainable, Thailand needs to attract good quality foreign tourists to revisit the country. It is very mportant for people and agencies involved to acquire the knowledge on factors and issues that matter to repeating visitors. Therefore, this study is undertaken to explore the determinants of revisit tourists' satisfaction towards Thailand's tourism services. The study uses both primary and secondary data. Questionnaire survey is conducted in Bangkok with 420 foreign tourists. To analyze data, samples are divided, according to their education levels, into 2 groups: quality and general tourists. Apart from descriptive statistics, F-test and ANOVA are used to analyze the difference in tourists’ behaviors between quality and general tourists. The factors affecting foreign tourists’ decision to visit Thailand are analyzed using probit model together with marginal effects. The results show that tourists’ age and current country of residence can significantly influence their visit. Moreover, foreign tourists’ satisfaction towards personnel and procedure relating to the country’s tourism is statistically significant in explaining their visit to Thailand.